2020
DOI: 10.1002/nop2.637
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional survey to explore the prevalence and causes of occupational burnout syndrome among perioperative nurses in Saudi Arabia

Abstract: Aim To detect the level of burnout and its most significant causes among perioperative nurses. Design A descriptive quantitative cross‐sectional survey design. Methods Data on burnout and its most significant causes were collected by surveying 39 perioperative nurses in a regional hospital in Saudi Arabia using the Maslach Burnout Inventory and a self‐developed questionnaire. Descriptive statistics were used to perform statistical analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…Consistent with the present study, studies conducted by Almodibeg and Smith (2021), Nahid et al (2021), andImani et al (2022) have emphasized the role of factors such as lack of appreciation and inadequate pay, shortfall of nurses, lack or inadequate equipment, and inappropriate physical facilities in operating room nurses burnout. Ambiguity in the duties of operating room nurses was another issue that was expressed by study participants as a cause of burnout.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with the present study, studies conducted by Almodibeg and Smith (2021), Nahid et al (2021), andImani et al (2022) have emphasized the role of factors such as lack of appreciation and inadequate pay, shortfall of nurses, lack or inadequate equipment, and inappropriate physical facilities in operating room nurses burnout. Ambiguity in the duties of operating room nurses was another issue that was expressed by study participants as a cause of burnout.…”
Section: Discussionsupporting
confidence: 87%
“…In their study, Almodibeg and Smith stated that although the prevalence of burnout was low among operating room nurses, these individuals were at a high risk. Numerous factors such as high workload, insufficient salary, job risks and lack of organizational support were cited as the main causes of burnout ( Almodibeg and Smith, 2021 ). Limited studies on burnout of operating room nurses were found in Iran.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Adeeb Shahin et al, demonstrated that about 39% of the nurses had high EE, and 38% had high DP [ 11 ]. Another local study including thirty-nine perioperative nurses showed high EE levels in 87.2% of them [ 19 ]. Similarly, the nurses in our study scored high in each of the three burnout dimensions, resulting in more than 50% of the nurses with 56.8% and 71.6% prevalence of EE and DP, respectively with DP being the most prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors agree on the adverse job characteristics that are associated with burnout processes, especially in nursing employees ( Dall’Ora et al, 2020 ; Almodibeg and Smith, 2021 ; Boateng et al, 2021 ). In addition, the negative consequences that this exhaustion process has both on organizations, affecting the quality of the service they provide ( Leon-Perez et al, 2016 ), and on their lives, developing mental ( Ding et al, 2014 ) and psychosomatic disorders ( Guerrero-Barona et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%